Narcissism and the Self - Behrendt, R. author. aut Link
XIV, 408 p.
Keywords: The book examines how coevolved intraspecific aggression and appeasement gestures can give rise to complex social, cultural, and psychopathological phenomena. It argues that the individual's need regulate narcissistic supplies and maintain feelings of safety is the overriding determinant of human conduct and thought in mental health and illness.